Single-center retrospective analysis of 454 culture-positive patients with tinea capitis and measurement of pathogens regarding thermal tolerance at 37°C - Xia, Xiujiao; Li, Jiajia; Zhi, Huilin; Liu, Zehu (Frontiers in Medicine, 2025)
BackgroundThis study aimed to analyze the epidemiological characteristics of tinea capitis (TC) and the changing trend of the pathogenic fungal spectrum in Hangzhou to assess the thermal tolerance of these pathogenic dermatophytes at 37°C.MethodsClinical, demographic, and mycological data of 454 TC patients were retrospectively collected.ResultsAmong children with TC, 198 were females and 201 were males, with a median age of 5 years. Among adults, there were 44 patients with TC among females and 11 patients with TC among males with a median age of 65 years. Microsporum canis was the most common pathogen (311, 68.50%), followed by Trichophyton violaceum (48, 10.57%), T. tonsurans (35, 7.71%), and T. mentagrophytes complex (30, 6.61%). The proportion of M. canis in the children group and adult group was 73.43% and 32.73%, respectively. After subculture, visible growth at 25°C were observed in 381 isolates, and 351 grew at 37°C. Compared to the proportion growing at 37°C, the proportion growing at 25°C was significantly greater for isolates from gray patch, M. canis, and T. mentagrophytes complex. There was no significant difference in the proportion growing at the two temperatures for other isolates, and all 10 strains of Nannizzia gypsea grew well at 37°C.ConclusionMicrosporum canis is the dominant pathogen of TC. Elderly women (postmenopausal women) were the main affected group of adult TC, and the proportion of anthropophilic dermatophytes in the adult group was significantly higher than that in the children group. Most dermatophytes were well tolerated at 37°C, particularly N. gypsea.